The unwavering resilience of scientific research in Latin America - González-Paz, Lenin (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2025)
Science in Latin America develops in an environment marked by constant adversity, and empirical research in our region is a living testimony to human strength. From laboratories with infrastructural limitations in South American public institutions to the most advanced innovation centres in Central America, academics have demonstrated an extraordinary ability to forge ahead despite fiscal constraints, brain drain and socio-economic ups and downs. This tenacity goes beyond mere survival: it is a collective effort that redefines what seems possible.